The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/aem.66.11.4921-4925.2000
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of Salmonella spp. at Reduced Water Activity and Its Effect on Heat Tolerance

Abstract: The effect of habituation at reduced water activity (a w ) on heat tolerance of Salmonella spp. was investigated. Stationary-phase cells were exposed to a w 0.95 in broths containing glucose-fructose, sodium chloride, or glycerol at 21°C for up to a week prior to heat challenge at 54°C. In addition, the effects of different a w s and heat challenge temperatures were investigated. Habituation at a w 0.95 resulted in increased heat tolerance at 54°C with all solutes tested. The extent of the increase and the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 43 publications
2
64
1
2
Order By: Relevance
“…Because the formation of filaments is associated with stress, it is reasonable to assume that stress protection processes are induced that frequently result in cross-protection; however, this has not been investigated in depth. For example, habituation of Salmonella to low a w increased its tolerance to heat (23) and sodium hypochlorite (19) compared to control cells. Of the various stress conditions tested in this study, growth of filament populations in the presence of 10% bile salts and the reduced rate of lethality at pH 2.0 were the most noticeable differences in comparison to control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because the formation of filaments is associated with stress, it is reasonable to assume that stress protection processes are induced that frequently result in cross-protection; however, this has not been investigated in depth. For example, habituation of Salmonella to low a w increased its tolerance to heat (23) and sodium hypochlorite (19) compared to control cells. Of the various stress conditions tested in this study, growth of filament populations in the presence of 10% bile salts and the reduced rate of lethality at pH 2.0 were the most noticeable differences in comparison to control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Low-a w TSB (pH 6.5; Oxoid Ltd.) was prepared as described previously (45) using AnalaR grades of glucose and fructose (in equal proportion) and sucrose or NaCl (BDH, Poole, Dorset, United Kingdom) as the humectants. The a w of the broth was adjusted by adding TSB (rvp 0.99: pH 6.5) to give rvp values between 0.65 and 0.90 and measured at 25°C using an Aqualab CX-3T (Labcell, Basingstoke, Hampshire, United Kingdom) water activity meter with an accuracy of Ϯ0.003.…”
Section: Methodsmentioning
confidence: 99%
“…Serovar Napoli (20), serovar Agona (37), and S. enterica serovar Java (3) were selected to represent a wide range of serovars and relevant low-a w sources. Bacterial strains were recovered from storage at Ϫ20°C, and stationary-phase cultures were prepared in tryptone soy broth (TSB; Oxoid Ltd., Basingstoke, Hampshire, United Kingdom) as described previously (45).…”
Section: Methodsmentioning
confidence: 99%
“…Using laboratory models, it was demonstrated that reducing water activity either by desiccation (24,31) or by addition of solutes (2,12,30,37,38) resulted in increased thermal tolerance. Furthermore, low-water-activity medium (30) and dry environment (24) were found to enhance Salmonella tolerance to sodium hypochlorite and ethanol, respectively.…”
mentioning
confidence: 99%